Definition of guilt or lack of guilt of individuals with intellectual disabilities under criminal procedure - Ahomed Chávez, Omar Abraham (2022)
This scientific paper analyzes how reasonable adjustments should be applied in a criminal procedure against defendants with cognitive intellectual disabilities in order to respect their right to due process.